Genotyping-by-sequencing of Illicium difengpi highlights its potential genetic diversity and conservation status - Ben Qin; Ying Hu; Yanfen Huang; Ying Liang; Xiaoyun Guo; Baoyou Huang (Scientific Reports)
Abstract Illicium difengpi is a critically endangered plant endemic to the karst mountains of Guangxi, China. Because of its medicinal and ecological values, many efforts were made on assessing the medicinal usage, natural history, ex-situ conservation, and stress tolerance of I. difengpi. Due to its extensive genome, whole genome sequencing has not been completed, and there has been limited research on its population genetics. Using genotyping-by-sequencing, we analyzed the single nucleotide polymorphism of 43 samples from 13 different sites, encompassing all the natural habitats of the species. The results showed that I. difengpi has low genetic diversity, which is exemplified by low heterozygosity, polymorphism information content, nucleotide diversity, and small effective population size (80–90). Also, the fixation index indicated that most subpopulations were highly differentiated, presumably due to their geographic isolation. This is a warning that I. difengpi is in real and immediate danger of extinction. Moreover, evolutionary relationship, principal component analysis, and Admixture all suggest that there is an obvious correlation between the geographic and genetic characteristics of I. difengpi. According to our results we suggest conservation strategies to safeguard its sustainability in the future.